Length (L): 2w + 6
width (w): w
Perimeter (P) = 2L + 2w
240 = 2(2w + 6) + 2(w)
240 = 4w + 12 + 2w
240 = 6w + 12
228 = 6w
38 = w
Length (L): 2w + 6 = 2(38) + 6 = 76 + 6 = 82
Answer: width = 38 ft, length = 82 ft
Although you didn't provide any answer choices:
A trinomial is an expression with exactly three terms that can't be combined an example would be this
x^2 - 3x + 1
None of those terms can be combined
x^2 + 3 - 4 has three terms but it isn't considered a trinomial because you can simplify it to x^2 - 1 which is known as a binomial because it has 2 terms in it's simplified form.
hope this helps C:
Answer:
29/60
Step-by-step explanation:
probability of playing is 290/600 which when simplified is29/60
Answer:
![\left[\begin{array}{ccc}3&-1&\\-1&1/2\\\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D3%26-1%26%5C%5C-1%261%2F2%5C%5C%5Cend%7Barray%7D%5Cright%5D)
Step-by-step explanation:
The matrix system for the linear equations: x + 2y = 8, 2x + 6y = 9
![\left[\begin{array}{ccc}1&2&\\2&6\\\end{array}\right] \left[\begin{array}{ccc}x\\y\end{array}\right] = \left[\begin{array}{ccc}8\\9\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1%262%26%5C%5C2%266%5C%5C%5Cend%7Barray%7D%5Cright%5D%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7Dx%5C%5Cy%5Cend%7Barray%7D%5Cright%5D%20%3D%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D8%5C%5C9%5Cend%7Barray%7D%5Cright%5D)
To get the coefficient of x and y, the inverse of the first matrix (let the first matrix be A) must be known.
= (1 / determinant of A) x Adjoint of A
the determinant of A = (1 x 6) - (2 x 2) = 6 - 4 = 2
Adjoint of A = ![\left[\begin{array}{ccc}6&-2&\\-2&1\\\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D6%26-2%26%5C%5C-2%261%5C%5C%5Cend%7Barray%7D%5Cright%5D)
=
= ![\left[\begin{array}{ccc}3&-1&\\-1&1/2\\\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D3%26-1%26%5C%5C-1%261%2F2%5C%5C%5Cend%7Barray%7D%5Cright%5D)
The length of the base 3 times the width. And we need to express the surface. I'm assuming the surface of the base. So, to get the area of the base, multiply w * l.